2007
DOI: 10.1158/0008-5472.can-07-0651
|View full text |Cite
|
Sign up to set email alerts
|

Peroxiredoxin 1 Interacts with Androgen Receptor and Enhances Its Transactivation

Abstract: Although hypoxia is accepted as an important microenvironmental factor influencing tumor progression and treatment response, it is usually regarded as a static global phenomenon. Consequently, less attention is given to the impact of dynamic changes in tumor oxygenation in regulating the behavior of cancer cells. Androgen receptor (AR) signaling plays a critical role in prostate cancer. We previously reported that hypoxia/ reoxygenation, an in vitro condition used to mimic an unstable oxygenation climate in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
80
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 47 publications
4
80
0
Order By: Relevance
“…Peroxiredoxin family members also regulate proliferation, in part through intracellular signaling cascades that apply hydrogen peroxide as a molecular second messenger. No known roles for PRDX4 have been described in the context of development, although other peroxiredoxin family members interact with the androgen receptor (AR) and modulate ARmediated signaling (44). All of the prostate cancer studies we evaluated showed elevated expression of PRDX4 in neoplastic lesions.…”
Section: Discussionmentioning
confidence: 95%
“…Peroxiredoxin family members also regulate proliferation, in part through intracellular signaling cascades that apply hydrogen peroxide as a molecular second messenger. No known roles for PRDX4 have been described in the context of development, although other peroxiredoxin family members interact with the androgen receptor (AR) and modulate ARmediated signaling (44). All of the prostate cancer studies we evaluated showed elevated expression of PRDX4 in neoplastic lesions.…”
Section: Discussionmentioning
confidence: 95%
“…For example, Prx I interacts with the oncoprotein c-Abl to inhibit its tyrosine kinase activity (13) and regulates AKT activation through preserving PTEN activity (14). In prostate cancer cells, Prx I interacts with androgen receptor, enhances its transactivation activity, and contributes to the aggressive cancer phenotype (15). Prx II is a negative regulator of platelet-derived growth factor (PDGF) receptor-mediated cell signaling (16) and a negative regulator of nuclear factor-kappa B (NF-κB) activation in mouse fibroblasts (17).…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that Prx1 may act as a molecular chaperone, and modulate the activities of growth regulatory proteins with an outcome favoring cell survival (17,20,25,26). Based on the results from a combination of mutagenesis, biochemical, and X-ray crystallographic studies, we recently reported that despite >90% homology in their amino acid sequences, human Prx1 and Prx2 proteins are structurally and functionally distinguishable (27).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated Prx1 was implicated in the chemotherapy resistance of breast cancer (16) and in radiotherapy resistance of lung cancer cells (17). On the other hand, down-regulation of Prx1 was shown to sensitize lung cancer cells to radiation and reduce metastasis (18,19), and to increase the sensitivity of prostate cells to androgen ablation treatment (20). Similarly, overexpression of Prx2 rendered leukemia and stomach cancer cells resistant to various chemotherapeutic agents (21,22), whereas downregulation of Prx2 sensitized head and neck cancer cells to radiation and gastric carcinoma to cisplatin (23,24).…”
mentioning
confidence: 99%